1998
DOI: 10.1128/mcb.18.8.4409
|View full text |Cite
|
Sign up to set email alerts
|

Three Small Nucleolar RNAs Identified from the Spliced Leader-Associated RNA Locus in Kinetoplastid Protozoans

Abstract: First characterized in Trypanosoma brucei, the spliced leader-associated (SLA) RNA gene locus has now been isolated from the kinetoplastids Leishmania tarentolae and Trypanosoma cruzi. In addition to the T. brucei SLA RNA, both L. tarentolae and T. cruzi SLA RNA repeat units also yield RNAs of 75 or 76 nucleotides (nt), 92 or 94 nt, and ϳ450 or ϳ350 nt, respectively, each with significant sequence identity to transcripts previously described from the T. brucei SLA RNA locus. Cell fractionation studies localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 60 publications
3
46
1
Order By: Relevance
“…The 270-nt RNA Present in the SLA1 Locus Is the Trypanosome snR30 Homologue-The 270-nt RNA was described as part of the SLA1 locus (48) and was shown to be immunoprecipitated by anti-fibrillarin antibody, suggesting that it belongs to the C/D family (49). However, this RNA can be folded, as can the canonical structure of snR30 (illustrated in Fig.…”
Section: Sla1 Depletion Eliminates the ⌿28 Of The Sl Rna And Also Affmentioning
confidence: 99%
See 1 more Smart Citation
“…The 270-nt RNA Present in the SLA1 Locus Is the Trypanosome snR30 Homologue-The 270-nt RNA was described as part of the SLA1 locus (48) and was shown to be immunoprecipitated by anti-fibrillarin antibody, suggesting that it belongs to the C/D family (49). However, this RNA can be folded, as can the canonical structure of snR30 (illustrated in Fig.…”
Section: Sla1 Depletion Eliminates the ⌿28 Of The Sl Rna And Also Affmentioning
confidence: 99%
“…The 270-nt Species Is the snR30 Homologue and Guides RNAs with Special Functions-The finding of the 270-nt species in the SLA1 locus suggests that this locus encodes for snoRNA with special functions, such as the SLA1 (48). The other small RNAs present in this locus, the C/D snoRNAs 76 and 92 are also nonconventional snoRNAs that may function in rRNA endonucleolytic cleavages.…”
Section: Modifications On U Snrnas Are Carried Out In Part By H/aca-imentioning
confidence: 99%
“…It was found that the trypanosomatid snoRNAs do not obey the general methylation rules. More specifically, the methylation sites corresponding to the duplex formed between the snoRNA and the target site are located either 1 or 6 nucleotides upstream from box D or DЈ (34). More recently, 17 box C/D snoRNAs were analyzed from T. brucei (35) by immunoprecipitation using antibodies against the cloned T. brucei fibrillarin protein.…”
mentioning
confidence: 99%
“…In addition, the SLA1 locus also carries both SLA1 and three C/D RNAs (27,35). All the clusters analyzed so far are transcribed as polycistronic snoRNA precursors by RNA polymerase II RT-PCR was performed as described under "Experimental Procedures" with oligonucleotides Neo and B2-tag-long.…”
Section: Discussionmentioning
confidence: 99%